2014
DOI: 10.1177/1078155214559114
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence to oral cancer therapy: The promising role of the pharmacist

Abstract: Medication adherence to oral cancer therapy is a critical component to achieving optimal patient outcomes. As the US population ages, growing numbers of patients will be prescribed oral cancer therapy regimens, highlighting the need for innovative and scalable solutions. Clinical pharmacists offer tremendous promise to help patients improve their adherence to oral cancer therapy. Moreover, addition of oral chemotherapy to Centers for Medicare & Medicaid Services (CMS) medication adherence quality measures has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…19 Communitybased oncology pharmacists play key roles within multidisciplinary teams involving nurses, oncologists, and primary care physicians, in delivering patient education and AE monitoring and management programs aimed at improving the management of AEs. 13,17,19,[21][22][23] Routine implementation of pharmacist-led drug monitoring programs has been shown to have a significant impact on clinical outcomes and health care costs of a number of chronic diseases. 24,25 In oncology, a retrospective observational cohort study of a pharmacist-managed oral chemotherapy management clinic that provided services (including education on oral chemotherapy agents, concurrent medications, symptom management, and insurance assistance) to cancer patients for up to three months found that the program led to reductions in rates of adverse effects, nonadherence, drug interactions, and medication errors over time, as well as potential cost avoidance or cost savings.…”
Section: Introductionmentioning
confidence: 99%
“…19 Communitybased oncology pharmacists play key roles within multidisciplinary teams involving nurses, oncologists, and primary care physicians, in delivering patient education and AE monitoring and management programs aimed at improving the management of AEs. 13,17,19,[21][22][23] Routine implementation of pharmacist-led drug monitoring programs has been shown to have a significant impact on clinical outcomes and health care costs of a number of chronic diseases. 24,25 In oncology, a retrospective observational cohort study of a pharmacist-managed oral chemotherapy management clinic that provided services (including education on oral chemotherapy agents, concurrent medications, symptom management, and insurance assistance) to cancer patients for up to three months found that the program led to reductions in rates of adverse effects, nonadherence, drug interactions, and medication errors over time, as well as potential cost avoidance or cost savings.…”
Section: Introductionmentioning
confidence: 99%
“…Patient education and adherence is an integral part of successful oral chemotherapy treatment and is often a collaborative effort among patients, family members, providers, and pharmacists. Successful patient counseling includes the indication, dosing regimen, supportive care, adverse effects, storage, and administration, as well as medication reconciliation [ 21 ]. One observational study quantified patient satisfaction after an initial pharmacy-led education encounter prior to starting chemotherapy and found that 86% of patients felt that meeting with a pharmacist was “absolutely necessary.” Furthermore, 83% of patients stated that they would be willing to pay for this pharmacy-driven service [ 4 ].…”
Section: Oral Chemotherapy Considerationsmentioning
confidence: 99%
“…Educating patients about medication characteristics, administration guidelines, and AEs may help reduce dose-modifying AEs and improve adherence. 70 Improvement in patient medication adherence was observed in a retrospective analysis of 56 patients taking oral TKIs and who were managed by oncology pharmacists. 71 In this study, the adherence rate in patients in the intervention group was 89% compared with 66% in patients receiving the usual care regimen.…”
Section: Follow-up Care Of Patientsmentioning
confidence: 99%